2018
DOI: 10.3390/geosciences8040117
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Debris-Induced Damage for Constructing Tsunami Fragility Curves for Buildings

Abstract: Catastrophe models quantify potential losses from disasters, and are used in the insurance, disaster-risk management, and engineering industries. Tsunami fragility and vulnerability curves are key components of catastrophe models, providing probabilistic links between Tsunami Intensity Measures (TIMs), damage and loss. Building damage due to tsunamis can occur due to fluid forces or debris impact; two effects which have different implications for building damage levels and failure mechanisms. However, existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…MAR refers to the case where the information is not MCAR but can be accounted for by using other attributes. The only study to analyze and treat missing data before conducting fragility function derivation is Macabuag et al (2016a). All other studies that produce fragility functions for various building classifications based on data from existing fragility functions may be susceptible to bias introduced by the removal of incomplete data-entries.…”
Section: Damage Data: Quality and Collection Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…MAR refers to the case where the information is not MCAR but can be accounted for by using other attributes. The only study to analyze and treat missing data before conducting fragility function derivation is Macabuag et al (2016a). All other studies that produce fragility functions for various building classifications based on data from existing fragility functions may be susceptible to bias introduced by the removal of incomplete data-entries.…”
Section: Damage Data: Quality and Collection Methodsmentioning
confidence: 99%
“…Studies that have compared TIMs have generally concluded that velocity alone is less effective than depth as an indicator of damage for buildings for the datasets investigated (Koshimura et al, 2009a,b;Macabuag et al, 2016a). However, velocity is often used to calculate the fluid force TIMs shown in Table 7.…”
Section: Summary Of Intensity Parametersmentioning
confidence: 99%
See 3 more Smart Citations